Change in Eyelid Closure in Spontaneous Blinking After Static Eyelid Reconstruction Surgery for Patients With Facial Paralysis. Issue 3 (13th March 2022) - Hidaka, Takeaki; Ogawa, Kazuya; Tomioka, Yoko; Yoshii, Kengo; Tomio, Jun; Okazaki, Mutsumi
Abstract : Background: Static eyelid reconstruction surgery, such as ptosis repair or brow lift, is widely performed for patients with facial paralysis. Complications include exposure keratitis and possible vision loss mainly due to eyelid closure impairment in spontaneous blinking. However, no quantitative evaluation data has been available regarding postoperative closure deterioration. Methods: To elucidate factors associated with postoperative eyelid closure impairment, a retrospective study was performed for 51 patients who underwent an initial static eyelid reconstruction surgery from October 2017 to August 2020. A static eyelid reconstruction surgery consisted of either 1 or more of the following: (1) levator advancement, (2) brow lift, and (3) orbicularis oculi myectomy. Eyelid closure ratios (0% for complete closure impairment and 100% for perfect closure) at spontaneous blinks were measured on 6 occasions: before operation and at postoperative 1, 3, 6, 9, and 12 months. Comparison was made between preoperative and postoperative values by using mixed-effects model. Results: Overall, average closure ratio was significantly increased. However, 10 patients had >10% closure ratio decreases at at least 1 postoperative measurement point, and all those patients had undergone brow lift procedures. Conclusions: Although eyelid closure at spontaneous blinks may, contrary to assumptions, generally be improved after static eyelid reconstruction surgery, brow lift was suggested to be associated with eyelid closure impairment.